Cassava Farming Partnership Model in Glugur Rimbun Land, Sampecita Village, Kutalimbaru District (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study aims to analyze the partnership pattern of farmers with cassava processing companies, the influence of production factors (seed area, labor and fertilizer) and farmer income analysis, to determine the feasibility of farming. The partnership pattern carried out between farmers/landowners and UD. Kreasi Lutvi is structured in a cooperation contract, where the partner UD. Kreasi Lutvi is responsible for cassava cultivation, providing production facilities ranging from seeds, herbicides, fertilizers, agricultural tools and labor and buying cassava harvests at an agreed price. Farmers provide land and supervisors in cassava cultivation activities until harvest. The feasibility analysis of the cassava business is as follows: production costs incurred per ha of Rp 14,500,000.00, - the amount of cassava production per ha is 23,405, - kg, selling price Rp. 1,450,-/kg, total revenue of Rp 33,937,250,-/ha and income of Rp.19,437,250.00,-./ha The R/C value is 2.34. This shows that the cassava business in the Glugur Rimbun land is feasible to be pursued